2009
DOI: 10.1111/j.1365-313x.2009.03817.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NF‐YB subunits LEC1 and LEC1‐LIKE activate transcription by interacting with seed‐specific ABRE‐binding factors

Abstract: SUMMARYLEAFY COTYLEDON 1 (LEC1) plays vital roles in the regulation of seed maturation in Arabidopsis. LEC1 encodes a homolog of yeast HAP3 or mammalian NF-YB/CBF-A subunit of trimeric CCAAT binding factor (CBF). Among the nine paralogs of NF-YB in Arabidopsis, LEC1-LIKE (L1L) is most closely related to LEC1, and can complement the lec1 mutation when expressed under the control of the LEC1 promoter. Although the nature of the B3-type seed maturation regulators as transcription factors have been investigated, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
210
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(219 citation statements)
references
References 62 publications
9
210
0
Order By: Relevance
“…In addition, FUS3 directly associated with AGL15 and BBM, which, like LEC1 and L1L, can promote somatic embryogenesis. L1L has been reported to interact with bZIP67, the gene for which is also potentially regulated by FUS3, and these factors together control the expression of CRC (At4g28520) and SUS2 (At5g49190; Yamamoto et al, 2009). FUS3 also directly up-regulates LBD40, which may be a direct target of ABI3 and LEC2 (Braybrook et al, 2006) as well.…”
Section: Fus3 Embryo Transcription Factors and The Afl/ Val Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FUS3 directly associated with AGL15 and BBM, which, like LEC1 and L1L, can promote somatic embryogenesis. L1L has been reported to interact with bZIP67, the gene for which is also potentially regulated by FUS3, and these factors together control the expression of CRC (At4g28520) and SUS2 (At5g49190; Yamamoto et al, 2009). FUS3 also directly up-regulates LBD40, which may be a direct target of ABI3 and LEC2 (Braybrook et al, 2006) as well.…”
Section: Fus3 Embryo Transcription Factors and The Afl/ Val Networkmentioning
confidence: 99%
“…VAL1 (with the redundant VAL2) information is from Suzuki et al (2007). The double blue lines indicate protein interaction (ABI3-ABI5 [Nakamura et al, 2001] and L1L-bZIP67 [Yamamoto et al, 2009]). Regulation of AtEM1 and AtEM6 (Bensmihen et al, 2002), of ABI5 (Lopez-Molina et al, 2002, and of fatty acid biosynthesis genes (Maeo et al, 2009) is also shown.…”
Section: Fus3 and Genes Regulated In Response To Supraoptimal Temperamentioning
confidence: 99%
“…Genetic studies with Arabidopsis have uncovered several genes that play major roles in seed development (9)(10)(11), including those that govern endosperm formation (12,13), embryo differentiation (14,15), and seed coat development (8). In addition, molecular studies with Arabidopsis and other plants have identified the ciscontrol regions of several genes active during seed development, particularly those encoding storage proteins, and the transcription factors (TFs) that play a role in their regulation (16)(17)(18)(19)(20)(21)(22). Nevertheless, the identities of most regulators of seed development and their direct targets are largely unknown.…”
mentioning
confidence: 99%
“…Additionally, several groups have demonstrated that each of the three plant NF-Y proteins can substitute their yeast counterparts in gene expression assays (Edwards et al, 1998;Masiero et al, 2002;Ben-Naim et al, 2006;Siefers et al, 2009). These observations indicate that plant NF-Y subunits might act as general transcription factors, as in mammals (Yamamoto et al, 2009). Although a complete functional plant NF-Y complex has not yet been described, the individual subunits are known to be involved in a number of important physiological processes, such as specific developmental processes and response to environmental stimuli (Lotan et al, 1998;Kusnetsov et al, 1999;Miyoshi et al, 2003;Ben-Naim et al, 2006;Combier et al, 2006;Wenkel et al, 2006;Cai et al, 2007;Nelson et al, 2007;Warpeha et al, 2007;Siefers et al, 2009).…”
Section: Gene Duplication Of Nf-y In Plantsmentioning
confidence: 99%